Predicting Genes in Single Genomes with AUGUSTUS. Issue 1 (22nd November 2018) - Hoff, Katharina J.; Stanke, Mario
Abstract: AUGUSTUS is a tool for finding protein‐coding genes and their exon‐intron structure in genomic sequences. It does not necessarily require additional experimental input, as it can be applied in so‐called ab initio mode. However, extrinsic evidence from various sources such as transcriptome sequencing or the annotations of closely related genomes can be integrated in order to improve the accuracy and completeness of the annotation. AUGUSTUS can be applied to single genomes, or simultaneously to several aligned genomes. Here, we describe steps required for training AUGUSTUS for the annotation of individual genomes and the steps to do the actual structural annotation. Further, we describe the generation and integration of evidence from various sources of extrinsic evidence. © 2018 by John Wiley & Sons, Inc.